2008
DOI: 10.1016/j.jadohealth.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drinks, Race, and Problem Behaviors Among College Students

Abstract: These findings suggest that energy drink consumption is closely associated with a problem behavior syndrome, particularly among whites. Frequent consumption of energy drinks may serve as a useful screening indicator to identify students at risk for substance use and/or other health-compromising behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

37
314
4
15

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(376 citation statements)
references
References 31 publications
(43 reference statements)
37
314
4
15
Order By: Relevance
“…Previous research on US college students also indicated higher consumption among White students, but the comparison was with Black students only. 17 Adolescents who reported tobacco use, cannabis use or nonmedicinal use of prescription drugs in the previous year, or reported binge drinking in the previous month, were at greater odds of having consumed an energy drink. These findings are consistent with findings from studies of college students that indicate that substance use behaviours tend to cluster within individuals.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous research on US college students also indicated higher consumption among White students, but the comparison was with Black students only. 17 Adolescents who reported tobacco use, cannabis use or nonmedicinal use of prescription drugs in the previous year, or reported binge drinking in the previous month, were at greater odds of having consumed an energy drink. These findings are consistent with findings from studies of college students that indicate that substance use behaviours tend to cluster within individuals.…”
Section: Discussionmentioning
confidence: 97%
“…The sparse research that has been conducted suggests that the consumption of energy drinks is correlated with heavy alcohol use, licit and illicit drug use, impulsivity, and risk-taking behaviours, including fighting and risky sexual behaviours. 7,10,[17][18][19] ABSTRACT OBJECTIVE: To examine energy drink consumption and its association with demographic characteristics, drug use, and injury among adolescents. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Co-administration of alcohol with ED resulted in increased alcohol consumption by the users of AwED (7) and users of AwED were more likely to exhibit high-risk behaviours, which included being more likely to take advantage of someone sexually or be taken advantage of sexually, riding with a driver who was under the influence of alcohol and being injured or requiring medical treatment (10,27) .…”
Section: Adolescents' Use Of Alcohol With Energy Drinksmentioning
confidence: 99%